Xinjiang Year Zero - Byler, Darren; Franceschini, Ivan; Loubere, Nicholas (ANU Press, 2022)
Since 2017, the Chinese authorities have detained hundreds of thousands of Uyghurs, Kazakhs and other Muslim minorities in 'reeducation camps' in China's northwestern Xinjiang autonomous region. While the official reason for this mass detention was to prevent terrorism, the campaign has since become a wholesale attempt to remould the ways of life of these peoples-an experiment in social engineering aimed at erasing their cultures and traditions in order to transform them into 'civilised' citizens as construed by the Chinese state. Through a collection of essays penned by scholars who have conducted extensive research in the region, this volume sets itself three goals: first, to document the reality of the emerging surveillance state and coercive assimilation unfolding in Xinjiang in recent years and continuing today; second, to describe the workings and analyse the causes of these policies, highlighting how these developments insert themselves not only in domestic Chinese trends, but also in broader global dynamics; and, third, to propose action, to heed the progressive Left's call since Marx to change the world and not just analyse it.